Proses Implementasi Program Sekolah Lapangan Cabai Rawit (Capsicum frutescens L.) - Afan Taufiqurohman; Sri Subekti (AGRITEXTS: Journal of Agricultural Extension, 2021)
Chili field school is one of the efforts to increase human resources and increase the productivity of chili crops through the development of human resources. The field school is a learning medium that can shape the behavior of local chili farmers. The purpose of this study is to explain the implementation of the field school program which is seen from the behavior of farmers (knowledge, attitudes, skills). The research method uses explanatory methods. Determining the location of the study with the purposive method. Determination of informants using purposive sampling. Data collection is done by interviews, observation and documentation. Data analysis using interactive models Miles and Huberman. Test the validity of the data using source triangulation. The results showed that all farmers experienced behavioral changes related to the study of polybag breeding, seed selection, spacing and control of chili plant organisms. In the study of tillage and liquid organic fertilizer, behavior changes occur in the majority of farmers, while only a minority of farmers experience behavioral changes related to the study of vegetable pesticides.